PERILAKU PEMBELIAN KONSUMEN TERHADAP SAYURAN SAWI DAN KOL SECARA ONLINE DI PO. ELLFAZ VEGETABLES BANDUNGAN DI MASA PANDEMI COVID-19 - Agnes Marsela Sihaloho; Tinjung Mary Prihtanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The Covid-19 pandemic has changed people's behavior in meeting their daily needs, one of which is when shopping for vegetables. Consumption of vegetables is important to strengthen the immune system. Online media has also become a trend in the search for food needs, especially vegetables among the community during the Covid-19 pandemic. The purpose of this study was to determine the number of consumer purchases of mustard greens and cabbage online during the pandemic, and to determine the factors that influence the online purchase of mustard greens and cabbage during the Covid-19 pandemic, a study in PO. Ellfaz Vegetables Bandungan. Sampling technique by applying purposive sampling technique with respondents as many as 30 samples per each type of vegetable. The data analysis technique used descriptive analysis and multiple linear regression analysis. The results showed that the number of online purchases of mustard greens was 1.183 kg/person in a month, while cabbage vegetables were 1,083 kg/person in a month. Variables of the number of family members, age, and education have a significant effect on consumer purchases of mustard greens and cabbage online, while the variables of product quality, perception of purchasing media, and income have no effect on consumer purchases of mustard greens online at PO. Ellfaz Vegetables Bandungan. In cabbage, there are no variables that affect the online purchase of cabbage at PO. Ellfaz Vegetables Bandungan during the Covid-19 pandemic.